Perspectives and challenges for mother-to-child transmission of HIV, hepatitis B, and syphilis in Brazil - Miranda, Angelica E.; Santos, Patricia C.; Coelho, Ronaldo A.; Pascom, Ana Roberta P.; de Lannoy, Leonor Henriette; Ferreira, Ana Cristina Garcia; Gaspar, Pamela Cristina; Maciel, Ethel Leonor; Barreira, Draurio; Pereira, Gerson Fernando Mendes (Frontiers in Public Health, 2023)
Background: Eliminating mother-to-child transmission (MTCT) of HIV, hepatitis B, and syphilis is a challenge in Brazil. Many policies have been implemented since 1986, but important gaps remain. This study aimed to describe the trends of MTCT in Brazil and evaluate the gaps and perspectives in this scenario.Methods: This is a descriptive study conducted with secondary data publicly available in the information systems of the Brazilian Ministry of Health regarding data on HIV, syphilis, and hepatitis B in pregnant women and children from 2011 to 2021.Results: HIV and hepatitis B have had constant rates over the years in pregnant women, with the detection rates around 0.5/1,000 live birth (LB) and 2.5/1.000LB, respectively. The same did not happen with syphilis, which has shown an increasing line in the last decade. In 2011, the detection rate of syphilis in pregnancy was 4.7/1,000LB, and in 2021 it reached 27.1/1,000LB. Regarding the trends in children, an important decrease was observed in HIV/AIDS (incidence rate from 0.17/1,000 in 2011 to 0.04/1,000 in 2021) and Hepatitis B (incidence rate from 0.9/1,000LB in 2011 to 0.5/1,000LB in 2021). For congenital syphilis, there is a continuous increase, being 3.3/1,000LB in 2011 and 9.9/1,000LB in 2021. Data from the HIV clinical monitoring showed that antiretroviral treatment coverage among pregnant women identified increased slightly between 2011 and 2021, in Brazil, from 92.3% to 94.3%. For syphilis, 82.5% of pregnant women were treated with benzathine penicillin, and 88.7% in 2011. The historical series of hepatitis B vaccination coverage in children has decreased over the years; it was 96% in 2013 and 76% in 2021.These data show many gaps and some perspectives in the MTCT program in Brazil. The country is close to reaching MTCT HIV elimination, but there are many challenges regarding HBV and syphilis. These data can be used to organize the strategies to improve the Brazilian response to MTCT elimination of HIV, hepatitis B, and syphilis.